1978
DOI: 10.1111/j.1745-9125.1978.tb00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Narcotic Addiction and Crime

Abstract: Arrest rates and self‐reported criminal behavior are examined as a function of frequency of narcatic use during the addiction careers first daily narcatic use to last daily use) of a sample of 690 admissions to the California Civil Addict Program. Thirty‐five percent of the addiction career non‐incarcerated time involved less‐than‐daily or no narcatic use. During these periods. arrest rates for property crimes and self‐reported criminal behavior were substantially lower than for periods of daily use. This appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 6 publications
2
35
0
1
Order By: Relevance
“…Their results clearly indicated a direct relationship between the addicts' intensity of drug use and the magnitude of their criminal behavior: The average number of crime days per year at risk was four to six times higher when these individuals were addicted than when they were involved in little or no illicit drug use. Similar findings were obtained at UCLA by McGlothlin and associates (Gropper 1985;McGlothlin, Anglin & Wilson 1978) in their study of 753 Southern Californian White and Hispanic heroin addicts who had been admitted to methadone maintenance programs.…”
Section: Further Examination Of the Association Between Heavy Marijuasupporting
confidence: 81%
“…Their results clearly indicated a direct relationship between the addicts' intensity of drug use and the magnitude of their criminal behavior: The average number of crime days per year at risk was four to six times higher when these individuals were addicted than when they were involved in little or no illicit drug use. Similar findings were obtained at UCLA by McGlothlin and associates (Gropper 1985;McGlothlin, Anglin & Wilson 1978) in their study of 753 Southern Californian White and Hispanic heroin addicts who had been admitted to methadone maintenance programs.…”
Section: Further Examination Of the Association Between Heavy Marijuasupporting
confidence: 81%
“…Self-reports on problem behaviors, such as drug use is suspect for both under-and overreporting (McCord, 1990), particularly because of the illegality of the behavior, which can lead to distortions in study outcomes. For example, studies that have employed confidential self-report interview methods assessing for criminal illegal behavior (i.e., crimes actually committed) resulted in gross underestimates (McGlothin, Anglin, & Wilson, 1978). In addition, there is large room for general errors in recalling information about events that occurred years earlier with self-report data.…”
Section: Limitationsmentioning
confidence: 99%
“…13 Chaiken and Chaiken (1984); Elliott and Huizinga (1984) ;Goldstein, et al (1991); Harrison and Gfroerer (1992); Dembo, et al (1994) 14 Studies of offending patterns by narcotic addicts during periods of varying levels of drug use include McGlothlin, et al (1978), Ball, et al (1981, Ball, et al (1983), Shaffer, et al (1984), Nurco, et al (1985), Nurco, et al (1986), Nurco, et al (1988), Speckart (1986, 1988), Speckart and Anglin (1986a). Relying on panel data from general population samples of juveniles, two studies examine temporal patterns in initiation of drug use and delinquency (Huizinga et al, 1989;van Kammen and Loeber, 1994).…”
Section: Focus On Changing Rates Of Offendingmentioning
confidence: 99%
“…20 Of the studies identified in note 14, McGlothlin, et al (1978), Nurco, et al (1986), Nurco, et al (1988), and Anglin and Speckart (1986,1988) explicitly examine the same sample during periods of heavy and light use (usually distinguished by daily and less than daily use of narcotic drugs). The changes in offending relate specifically to drug or property offenses.…”
mentioning
confidence: 99%